The Effect Of Acupuncture Therapy Combined With Fire Cupping on Changes In Pain Scale and BPFS In Low Back Pain Cases In Cluntang Village Musuk District, Boyolali Regency - David Tri Wahyudi; Imrok Atus Sholihah; Sri Yatmihatun (Indonesian Journal of Acupuncture, 2026)
Low back pain is a musculoskeletal disorder caused by unergonomic work postures, affecting pain scale and functional ability. Acupuncture and fire cupping therapy are known to effectively reduce pain and improve blood circulation. This study aims to determine the effect of the combination of both on changes in pain scale and BPFS in 36 subjects in Cluntang Village, Musuk District, Boyolali, from October 2024 to March 2025. Using a quasi- experimental method with a two-group pretest- posttest design (acupuncture combined with fire cupping and fire cupping alone), the Mann-Whitney test results showed a p value > 0.05, which means there is no significant difference between groups. In conclusion, both therapies were equally effective in reducing the pain scale and improving the functional ability of BPFS, although there was no significant difference between them.